Contrast-Enhanced Ultrasound: Practical Review for the Assessment of Hepatic and Renal Lesions. Issue 2 (June 2016) - Denham, Stephanie LeeAnn Wilson; Alexander, Lauren F.; Robbin, Michelle L.
Abstract : Abstract: The use of microbubble contrast greatly enhances the ability of ultrasound to delineate structures and therefore aid in diagnosis. Ultrasound microbubble contrast agents are composed of low-solubility gas encapsulated in a biomaterial shell. These agents use the physics of ultrasound imaging to effectively identify and characterize focal hepatic and renal lesions. Not only can contrast agents be used to evaluate multiple phases of lesion contrast enhancement, but ultrasound also allows for real-time study of enhancement patterns. The short half-life and intravascular location of the microbubbles allows for multiple, sequential administrations of contrast to observe enhancement of lesions in different sites. Furthermore, the ability to perform imaging without ionizing radiation and the lack of nephrotoxicity make contrast-enhanced ultrasound an ideal evaluation method for patients who need serial surveillance or in whom imaging options are severely limited because of renal insufficiency. These techniques are widely used in many countries for diagnostic radiological purposes; however, the lack of both Food and Drug Administration approval and reimbursement for noncardiac hospital-based imaging has delayed widespread use in the United States. Despite these limitations, continued research and innovations in ultrasound contrast make it essential to have a working knowledge of the typical enhancement patterns of frequently seen hepatic and renal lesions as these techniques offer an alternative option for contrast imaging. Abstract : Supplemental digital content is available in the text.